Two-Tier Test: Development of Critical Thinking Instruments for Ecosystem Concepts - Helda Dumayanti; Risda Putri Indriani; Evita Nury Hariyanti; Rizhal Hendi Ristanto; Mieke Miarsyah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Critical thinking is necessary in improving the quality of education. Students' critical thinking includes interpretation, analysis, evaluation, inference, interpretation, and self-regulation. The two-tier test instrument was developed to determine students critical thinking skills in the ecosystem at class X MIPA di MAN 1 Bogor City. This research method used was based on 4D development model (Define, Design, Develop, and Disseminate). The instrument was tested on two expert validators and 35 students. To test the success rate of the test, validation, reliability, and item analysis were used. The item anlaysis used is the level of difficulty of the questions and differentiating power of answer choice. Based on the results of the product trial, 10 valid questions and 5 unvalid questions. The reliability test result was 0,671 which the interpretation that 45% of respondents considered the instrument developed to be reliable. In addition, 10 questions are in the difficult category and 5 questions are in the medium category. The differentiating power of answer choice results was 1 question in the very good category, 6 questions in the good category, 4 questions in the moderate category, and 4 questions in the poor category. The two-tier test instrument for ecosystem critical thinking in this study is declared valid and reliable so this can be used as an instrument in student’s learning.